Pembangunan ekonomi melalui pengembangan pertanian - Sumodiningrat, Gunawan (Jakarta : Bina Rena Pariwara, 2000)
Agricultural development and Indonesian economy.
Includes bibliographical references (p. [133]-137) and index.
Keywords: Agriculture -- Economic aspects -- Indonesia; Agriculture and state -- Indonesia